Circadian rhythms and obesity: Timekeeping governs lipid metabolism. Issue 3 (7th August 2020) - Li, Yuying; Ma, Jie; Yao, Kang; Su, Wenxuan; Tan, Bie; Wu, Xin; Huang, Xingguo; Li, Tiejun; Yin, Yulong; Tosini, Gianluca; Yin, Jie
Abstract: Almost all living organisms have evolved autoregulatory transcriptional‐translational feedback loops that produce oscillations with a period of approximately 24‐h. These endogenous time keeping mechanisms are called circadian clocks. The main function of these circadian clocks is to drive overt circadian rhythms in the physiology of the organisms to ensure that main physiological functions are in synchrony with the external environment. Disruption of circadian rhythms caused by genetic or environmental factors has long‐term consequences for metabolic health. Of relevance, host circadian rhythmicity and lipid metabolism are increasingly recognized to cross‐regulate and the circadian clock‐lipid metabolism interplay may involve in the development of obesity. Multiple systemic and molecular mechanisms, such as hormones (ie, melatonin, leptin, and glucocorticoid), the gut microbiome, and energy metabolism, link the circadian clock and lipid metabolism, and predictably, the deregulation of circadian clock‐lipid metabolism interplay can increase the risk of obesity, which in turn may exacerbate circadian disorganization. Feeding time and dietary nutrients are two of key environmental Zeitgebers affecting the circadian rhythm‐lipid metabolism interplay, and the influencing mechanisms in obesity development are highlighted in this review. Together, the characterization of the clock machinery in lipid metabolism aimed at producing a healthy circadian lifestyle may improve obesity care.